2012
DOI: 10.4236/jbbs.2012.22020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Iron Deficiency on Olfactory Behavior in Weanling Rats

Abstract: Chronically high occupational exposure to airborne metals like iron can impair olfactory function, but little is known about how low iron status modifies olfactory behavior. To investigate the influence of body iron status, weanling rats were fed a diet with low iron content (4 – 7 ppm) to induce iron deficiency anemia and olfactory behavior was compared to control rats fed an isocaloric diet sufficient in iron (210 – 220 ppm). Iron-deficient rats had prolonged exploratory time for attractive odorants in behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Ruvin Kumara and Wessling‐Resnick have researched the relationship between low iron condition of the body and behavioral scent functions by using the iron deficiency anemia model induced by diet in rats. As a result of this research, they have found that iron deficiency changes the smelling behavior . This study supports the fact that oddity in smelling behavior of our cases caused by iron deficiency.…”
Section: Discussionsupporting
confidence: 89%
“…Ruvin Kumara and Wessling‐Resnick have researched the relationship between low iron condition of the body and behavioral scent functions by using the iron deficiency anemia model induced by diet in rats. As a result of this research, they have found that iron deficiency changes the smelling behavior . This study supports the fact that oddity in smelling behavior of our cases caused by iron deficiency.…”
Section: Discussionsupporting
confidence: 89%
“…Although research into the relationship between low ferritin and olfactory function in animals has been completed, the same has not been well tested in humans. In studies with rats, it is suggested that iron is a cofactor that controls behavioural olfactory function by participating in signalling through inhibitory pathways, and that iron has a key role in the synthesis of neurons involved in inhibition of odourant signals 14. In studies with piglets, the olfactory bulb was significantly different in size in piglets with severe iron deficiency, indicating the role of iron in other mechanisms 15.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that the predominant cause of pica associated with iron deficiency or depletion in adults is low tissue iron levels, possibly in the tongue, olfactory apparatus, or other locations in the brain [ 31 , 32 ]. In iron-deficient rats, mean blood 59 Fe levels after intranasal administration of the radioisotope as ferrous or ferric form were significantly higher than those of iron-sufficient control rats [ 33 ]. Divalent metal transporter-1 (DMT1) levels are significantly higher in the olfactory bulbs of iron-deficient rats [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In iron-deficient rats, mean blood 59 Fe levels after intranasal administration of the radioisotope as ferrous or ferric form were significantly higher than those of iron-sufficient control rats [ 33 ]. Divalent metal transporter-1 (DMT1) levels are significantly higher in the olfactory bulbs of iron-deficient rats [ 33 ]. Thus, the molecular mechanism of olfactory iron absorption and possibly of olfactory or gustatory function involves DMT1 and is influenced by body iron repletion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation